Efficacy and safety of the S-1, nab-paclitaxel, and gemcitabine triplet regimen in patients with resected pancreatic ductal adenocarcinoma - Ran, Donghui; Geng, Cheng; Cha, Zhongming; Nie, Xiaohan; Atigu, Abudouwaili; Zhao, Chuankui; Xu, Xinjian (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the safety, feasibility, and efficacy of an S-1-based triplet regimen (with nab-paclitaxel and gemcitabine) as adjuvant therapy following curative resection for pancreatic ductal adenocarcinoma (PDAC).MethodsWe retrospectively analyzed 3-year postoperative clinical data from 92 patients with PDAC who underwent curative resection between March 2020 and March 2022. Participants were allocated to either a control group (n = 40) receiving nab-paclitaxel plus gemcitabine (nab-P/GEM) or an experimental group (n = 52) receiving S-1 plus nab-paclitaxel plus gemcitabine. We compared overall survival (OS), disease-free survival (DFS), and adverse event (AE) incidence between groups.ResultsThe experimental group showed significantly longer median OS (28.9 vs. 20.9 months; HR 0.62, 95% CI 0.38–0.99; P = 0.049 by log-rank test) and DFS (19.5 vs. 13.6 months; HR 0.59, 95% CI 0.36–0.97; P = 0.036) compared with controls. The incidence of grade ≥3 AEs was significantly lower in the experimental group, including leukopenia (13.5% vs. 47.5%; P < 0.001) and neutropenia (15.4% vs. 70.0%; P < 0.001). Fewer patients in the experimental group required treatment discontinuation (1.9% vs. 12.5%) or dose modifications (13.5% vs. 65.0%).ConclusionThe S-1/nab-paclitaxel/gemcitabine triplet regimen appears to improve survival outcomes while demonstrating potentially favorable tolerability as adjuvant therapy for resected PDAC.